2023
DOI: 10.21037/jtd-22-1749
|View full text |Cite
|
Sign up to set email alerts
|

Chest tube-free video-assisted thoracoscopic surgery secured by quantitative air leak monitoring: a case series

Abstract: Background Although chest tube-omitted video-assisted thoracoscopic surgery (VATS) has been proven to be safe and efficacious, its universal application is precluded by a varying morbidity rate due to a lack of standardization. Since digital chest drainage has already shown improved accuracy and consistency in the management of postoperative air leak, we incorporated it in the strategy of intraoperative chest tube withdrawal, aiming to achieve better results. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lesser et al used a 24F chest tube and underwater seal drainage system [ 10 ]. Li et al inserted a central venous catheter via the intercostal region at another site from the utility incision and applied -8 cm H 2 O negative pressure to the catheter [ 13 ]. Liao et al checked the air leak with saline filling to the thoracic cavity and used a 7 mm-silicon CMW drain with a vacuum ball.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesser et al used a 24F chest tube and underwater seal drainage system [ 10 ]. Li et al inserted a central venous catheter via the intercostal region at another site from the utility incision and applied -8 cm H 2 O negative pressure to the catheter [ 13 ]. Liao et al checked the air leak with saline filling to the thoracic cavity and used a 7 mm-silicon CMW drain with a vacuum ball.…”
Section: Discussionmentioning
confidence: 99%
“…While Li et al found the rate of subcutaneous emphysema to be 27.2%, Liu et al reported a very low rate of 3.3%. Additionally, they could not find any cause or predisposing factors for this complication [ 13 , 15 ]. In our series, minimal subcutaneous emphysema around the utility incision, which was detected radiologically and had no clinical significance, occurred in 4 patients, and none of them required additional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Another method which was widely performed was the temporary insertion of a chest drain inside the pleural cavity (10,11,22,(24)(25)(26)(27)(28)(30)(31)(32)(33). After closing all the intra-operative chest wall incisions, the drain was subsequently either connected to a digital suction system with negative suction (24, 27, 28, 30, 31,35) or its extra-thoracic end was simply immersed to a bowl with sterile water (10,11,22,32) while the anesthetic team administered manually positive inspiratory pressures. Then if there was no air leak by both the anesthesiologist assessment of volume delivered and returned and by the digital air leak meter attached to the chest tube the chest drain was removed before extubation.…”
Section: Chest Tube Removal Prior To Leaving the Operating Roommentioning
confidence: 99%
“…[5][6][7] Typically, these tubes remain in place post-thoracic or cardiac surgery until the output decreases to less than 150 ml in 24 hours, and any air leaks are resolved. [8][9][10] Positioned in the pleural space rather than the lungs, chest tubes are inserted between the parietal and visceral pleurae. The outer layer, the parietal pleura, covering the chest wall www.pakheartjournal.com and diaphragm, contains a small amount of serous fluid, reducing friction and enhancing pleural surface adhesion.…”
Section: Introductionmentioning
confidence: 99%